Evaluasi Implementasi Desentralisasi di Indonesia: Keberhasilan dan Kegagalan - Fajria, Rahmah; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to evaluate the implementation of decentralization in Indonesia since the enactment of regional autonomy following the 1999 reform era. Decentralization was intended to bring public services closer to the people, strengthen local democracy, and enhance government efficiency. However, its implementation has produced mixed outcomes and various challenges. This article examines the successes of decentralization in encouraging public participation, increasing local government revenue, and accelerating infrastructure development. On the other hand, it also highlights several failures, such as weak local government capacity, widespread corruption at the regional level, and persistent development disparities among regions. The evaluation uses a qualitative approach, primarily through literature review and policy analysis. The findings reveal that the success of decentralization is heavily influenced by the quality of local governance, human resource capacity, and consistent regulatory support from the central government. Therefore, a reformulation of decentralization policy is needed one that is more adaptive and responsive to local dynamics—in order to achieve the full potential of regional autonomy.